Maqasid Al-Shariah Analysis of Marriage Annulment at the Cikarang Religious Court: A Case Study of Decision Number 1380/Pdt.G/2019/PA.Ckr - Ema Damayanti; Suprihatin; Musyaffa Amin Ash Shabah; Agus Supriyanto (Universitas Darunnajah Jakarta, Indonesia, 2025)
One of the things that can cause a marriage to end is the annulment of the marriage, such as in case number 1380/Pdt.G/2019/PA.Ckr concerning the annulment of marriage at the Cikarang Religious Court. This study aims to determine and analyze the judge's considerations in deciding the case with the maqoshid sharia approach to the decision. The research method used in this study is a descriptive analysis method with a qualitative research type. The approach used is normative juridical legal research using decision number 1380/Pdt/G/2019/PA.Ckr as the primary data source. The results of this study are that decision number 1380/Pdt.G/2019/PA.Ckr has legal coherence (legal conformity) with Law No. 1 of 1974 in conjunction with Law No. 16 of 2019 concerning Marriage, article 27 paragraph (2) and the Compilation of Islamic Law, article 27 paragraph (2) which states that a marriage annulment can be filed due to fraud or misunderstanding regarding the husband or wife during the marriage. Because in this decision case, it has been proven that there was fraud committed by Respondent 1, in which Respondent 1 covered up her condition of being pregnant before marrying the Applicant and the fetus was another man's child. And in terms of maqoshid sharia, the decision to annul the marriage in this decision is more beneficial for both of them than having to continue their marriage. Keywords: Marriage Annulment, Judge's Consideration, Maqoshid Syariah.